Industrialization meets sustainability: Analysing the role of technological innovations, energy efficiency and urbanisation for major industrialized economies - Onwe J.C.; Ullah E.; Ansari M.A.; Sahoo M.; Dhayal K.S. (Academic Press, 2025)
Considering how crucial environmental quality is to development, production often takes precedence over the development process when certain macroeconomic policies are being implemented. This phenomenon has been the subject of several studies conducted in various regions and nations. In this context, the recent article explores the nonlinear effects of industrial output, renewable energy, technological innovations, energy efficiency, and urbanization on CO2 emissions in the top ten industrialized countries. It recommends contradictory policy approaches due to its reported conflicting outcomes, opening up new research directions. To this end, the study relies on advanced econometric tools such as panel QARDL (Quantile Autoregressive Distributed Lag) and the nonparametric quantile Granger causality (NPQGC) test to attain robust results. The findings suggest that industrial output and urbanization significantly deteriorate environmental quality by increasing CO2 emissions across various time horizons. However, renewable energy, technological innovations, and energy efficiency have a significant influence towards enhancing environmental quality. Notably, industrialization and urbanization become environmentally friendly when energy efficiency is integrated with these variables. Additionally, the NPQGC test supports the main results by confirming the Granger causality between the modelled series. Based on the outcomes, the study suggests that the integration of energy efficiency with industrialization and urbanization can significantly contribute to achieving a sustainable environment. ? 2024 Elsevier Ltd